2003
DOI: 10.1002/polb.10648
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer and triplet exciton confinement in polymeric electrophosphorescent devices

Abstract: Energy transfer and triplet exciton confinement in polymer/phosphorescent dopant systems have been investigated. Various combinations of host‐guest systems have been studied, consisting of two host polymers, poly(vinylcarbazole) (PVK) and poly[9,9‐bis(octyl)‐fluorene‐2,7‐diyl] (PF), blended with five different phosphorescent iridium complexes with different triplet energy levels. These combinations of hosts and dopants provide an ideal situation for studying the movement of triplet excitons between the host po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
120
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 33 publications
10
120
0
4
Order By: Relevance
“…We expected poly(3,6-fluorene) might have wider bandgap and much higher triplet energy level than poly(2,7-fluorene), and as a result it could be a good conjugated host material for the blue-and green-light-emitting triplet guests. In this Communication, we report the synthesis of a novel conjugated homopolymer, poly (9,9 0 -bis(2-ethylhexyl)-3, 6-fuorene) (P36EHF), with a wide bandgap of 3.65 eV showing PL and electroluminescence (EL) emission in the UV region peaked at around 344 and 400 nm, respectively. We have also shown that P36EHF has a triplet energy level at around 2.6 eV much higher than that of poly(2,7-fluorene)s. Therefore P36EHF can be a good host material for green-and even blue-light-emitting triplet emitters, such as iridium(III) fac-tris(2-phenylpyridine) (Ir(ppy) 3 ) and iridium(III) bis [2-…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We expected poly(3,6-fluorene) might have wider bandgap and much higher triplet energy level than poly(2,7-fluorene), and as a result it could be a good conjugated host material for the blue-and green-light-emitting triplet guests. In this Communication, we report the synthesis of a novel conjugated homopolymer, poly (9,9 0 -bis(2-ethylhexyl)-3, 6-fuorene) (P36EHF), with a wide bandgap of 3.65 eV showing PL and electroluminescence (EL) emission in the UV region peaked at around 344 and 400 nm, respectively. We have also shown that P36EHF has a triplet energy level at around 2.6 eV much higher than that of poly(2,7-fluorene)s. Therefore P36EHF can be a good host material for green-and even blue-light-emitting triplet emitters, such as iridium(III) fac-tris(2-phenylpyridine) (Ir(ppy) 3 ) and iridium(III) bis [2-…”
mentioning
confidence: 99%
“…The detailed procedure for synthesis of the monomer and intermediates and their characterization can be found in the Supporting Information (SI). The nickel-catalyzed Yamamato coupling polymerization was employed to obtain the desired homopolymer, poly (9,9 0 -bis(2-ethylhexyl)-3,6-fluorene, in good yield (80%). The polymer was readily soluble in common organic solvents such as chloroform, tetrahydrofuran (THF), and toluene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dexter transfer was considered to be unlikely since the T 1 level of PVK is lower in energy than the T 1 level of dbm, ∼ 2.5 and 2.6 eV, respectively. [8,25] The expected efficacy of energy transfer was evaluated by estimating the Förster radius R 0 , defined as the acceptordonor distance at which the probability of Förster energy transfer is equal to that of donor de-excitation by fluorescence or other processes, as follows:…”
mentioning
confidence: 99%
“…10 Therefore, better matching between the host material and deep blue dopant material with sufficient spectral overlap for Förster energy transfer 11 is required for deep blue emission with high efficiency. [12][13][14][15][16][17][18][19][20] Also, an OLED's quantum efficiency is determined by the carrier injection and recombination in the emitting layer (EML); therefore, the balance between electrons and holes in the EML is the most important factor to obtain higher quantum efficiency. This study contributes to the understanding of significant effects of double EMLs and host-dopant systems of blue OLEDs with 4,4'-bis (9-ethyl-3-carbazovinylene)-1,1'biphenyl (BCzVBi) doped to two different host materials of 4,4-bis (2,2-diphenylyinyl)-1,10-biphenyl (DPVBi) and 9,10-bis (2-naphthyl) anthracene (ADN).…”
Section: Introductionmentioning
confidence: 99%